Vorsorgeuntersuchungen und Check-ups in der Pneumologie - Kroenig, Johannes; Holland, Angélique; Vogelmeier, Claus Franz (DMW - Deutsche Medizinische Wochenschrift, 2019)
In pneumology, preventive check-ups have played a subordinate role so far. Current research results could change this. In the following article the focus is on lung cancer and COPD, diseases that have a considerable influence on mortality and morbidity in modern society. Approaches will be discussed that will allow earlier diagnosis of COPD or identify patients at risk. In particular Capture, a questionnaire that significantly increases the pre-test probability in COPD diagnostics, should be mentioned here. Lung carcinoma screening is a controversial topic in Germany. In an American study, the relative mortality rate from lung cancer was significantly reduced by CT screening. Results of a European study (Nelson trial) are still pending. A high pre-test probability will also be decisive for lung cancer screening. In this way, the cost-benefit ratio could be optimized. Since COPD patients have a significantly increased risk of lung cancer, there might be overlaps in the screening procedures.
Keywords: Vorsorgeuntersuchungen; Lungenkarzinom; COPD; CAPTURE; NELSON